Single nucleotide polymorphisms and sickle cell disease-related pain: a systematic review - Gehling, Gina M.; Powell-Roach, Keesha; Wilkie, Diana J.; Dungan, Jennifer R. (Frontiers in Pain Research, 2023)
Background: Scientists have speculated genetic variants may contribute to an individual's unique pain experience. Although research exists regarding the relationship between single nucleotide polymorphisms and sickle cell disease-related pain, this literature has not been synthesized to help inform future precision health research for sickle cell disease-related pain. Our primary aim of this systematic review was to synthesize the current state of scientific literature regarding single nucleotide polymorphisms and their association with sickle cell disease-related pain. Methods: Using the Prisma guidelines, we conducted our search between December 2021-April 2022. We searched PubMed, Web of Science, CINAHL, and Embase databases (1998-2022) and selected all peer-reviewed articles that included reports of associations between single nucleotide polymorphisms and sickle cell disease-related pain outcomes.Results: Our search yielded 215 articles, 80 of which were duplicates, and after two reviewers (GG, JD) independently screened the 135 non-duplicate articles, we retained 22 articles that met the study criteria. The synthesis of internationally generated evidence revealed that this scientific area remains predominantly exploratory in nature, with only four studies reporting sufficient power for genetic association. Sampling varied across studies with a range of children to older adults with SCD. All of the included articles (n = 22) examined acute pain, while only nine of those studies also examined chronic pain.Currently, the evidence implicating genetic variation contributing to acute and chronic sickle cell disease-related pain is characterized by modestly powered candidate-gene studies using rigorous SCD-pain outcomes. Effect sizes and directions vary across studies and are valuable for informing the design of future studies. Further research is needed to replicate these associations and extend findings with hypothesis-driven research to inform precision health research.